Role of Macroeconomic Dynamics in Determining Government Debt: Evidence From Developing Economy - Muhammad Asif Hussain; Salman Ali Qureshi; Muhammad Munir Ahmad (International Journal of Business and Economic Affairs, 2023)
Pakistan is one of the growing countries that relies a lot on debt because of less tax revenue and more spending. Government debt is a significant economic issue in Pakistan. To solve this situation, we must look at the reasons behind Pakistan’s huge government debt. Studies in the past have mostly looked at the connections between government debt and economic growth, the debt-to-GDP ratio and economic growth, and a few other general debt-related problems. Time series data techniques are used in this paper to look at how macroeconomic factors affect government debt from 1980 to 2021. The ARDL approach results show that fiscal deficit, balance of trade, government spending, debt service, and currency exchange rate all have a strong positive link with government debt. However, the relationship between fiscal deficit, debt service, and currency exchange rate to government debt is positive and significant in both long and short terms, whenever government spending has only a short-term effect and balance of trade has a long-term on the government debt.